Investigation of an Outer Rotor In-Wheel Switched Reluctance Motor for Electric Vehicles by Finite Element Method - Omaç, Zeki (Fırat University, 2022)
The demand of fossil fuel vehicles has decreased due to carbon emissions. Recently, electric vehicles (EV) with electric motor propulsion have gotten attention due to their zero carbon emissions and high efficiency. In this study, an outer rotor in wheel switched reluctance motor (IWSRM) with 18 poles on the stator and 24 poles on the rotor, designed for the propulsion of electric vehicles, is investigated in two-dimensional Finite Element Method (FEM). The magnetic field distributions of IWSRM for different rotor positions at nominal current are obtained. Then, the torque and phase inductance are calculated. As a result, the designed IWRSM provided low torque.
Keywords: Engineering; Mühendislik